PENGARUH PERBEDAAN PROPORSI TEPUNG UBI JALAR UNGU DAN TEPUNG BERAS MERAH TERHADAP SIFAT FLAKES - Tejosaputro, Karina; Suseno, Thomas Indarto Putut; Jati, Ignasius Radix Astadi Praptono (Jurnal Teknologi Pangan dan Gizi, 2017)
Flakes products are consumed in the morning as breakfast because its preparation is very easy and only needs short period of time. The usage of purple sweet potato flour and red rice flour is to increase the economic value, besides the two ingredients have benefits for our body. Both materials have carbohydrates as a source of energy, dietary fibers, and anthocyanin that acts as antioxidants. The aim of this research was to study the effect of different proportions of purple sweet potato flour and red rice flour on chemical properties of flakes. The experimental design was Randomized Block Design with one factor, namely purple sweet potato flour and red rice flour proportions consisted of six levels including 100:0; 80:20; 60:40; 40:60; 20:80; 0:100% b/b with four replications. Chemical characteristics that were analyzed were moisture content, antioxidant activity by DPPH assay, dietary fiber content, and phenolic content. Data were analyzed using Analysis of Variance at α = 5%. If the ANOVA test showed a significant effect, data would be analyzed by Duncan’s Multiple Range Test at α = 5% to determine the level of treatment that gave a significant difference, continued with making a spider web graph to determine the treatment with the highest chemical characteristics. Differences in the proportion of purple sweet potato flour: red rice flour significantly effected the phenolic content, antioxidant activity by DPPH assay, and dietary fiber content. The results of the study on flakes was 4.25-5.71% moisture content, 390.469-886.406 mg GAE/100 g sample phenolic content, 52.26-65.24% antioxidant activity, and 9.47-13.86% dietary fiber content. The best treatment was the proportion of 100:0 purple sweet potato flour: red rice flour.